Impact of workplace bullying on job burnout and turnover intention among nursing staff in Greece: Evidence after the COVID-19 pandemic - Petros Galanis; Ioannis Moisoglou; Aglaia Katsiroumpa; Panayota Sourtzi (AIMS Press, 2024)
Introduction The prevalence of workplace bullying, job burnout, and turnover intention among nursing staff increased during the COVID-19 pandemic. However, to the best of our knowledge, there are no studies that have measured the relationships among variables of interest after the pandemic. Objective Our intention is to investigate the effect of workplace bullying on job burnout and turnover intention in nursing staff. Methods We conducted a cross-sectional study during January-February 2024 in Greece. We obtained a convenience sample of 450 nurses. We used the 22-item Negative Acts Questionnaire-Revised to assess workplace bullying. We measured job burnout with the single-item burnout measure. We measured nurses' turnover intention with a valid 6-point Likert scale. Results The study sample included 450 nurses with the mean age of 39.1 years (standard deviation [SD] = 10.2). The mean workplace bullying score was 7.7 (SD = 2.0), while the mean job burnout score was 7.7 (SD = 2.0). Among our nurses, 57.3% showed a high level of turnover intention. After eliminating confounders, we found that increased workplace bullying (adjusted beta = 0.031, 95% confidence interval [CI] = 0.023 to 0.039, p < 0.001) was associated with increased job burnout. Moreover, multivariable logistic regression analysis showed that increased turnover intention was more common among nurses who experienced higher levels of workplace bullying (adjusted odds ratio = 1.057, 95% CI = 1.043 to 1.071, p < 0.001). Conclusion We found a positive relationship between workplace bullying, job burnout, and turnover intention. Nurse managers, organizations, and policy-makers ought to consider such findings to intervene and decrease workplace bullying by improving working conditions.